2014
DOI: 10.1371/journal.pone.0114005
|View full text |Cite
|
Sign up to set email alerts
|

Serum OPN Expression for Identification of Gastric Cancer and Atrophic Gastritis and Its Influencing Factors

Abstract: BackgroundMost studies have found that osteopontin (OPN) expression level is related to the poor prognosis of gastric cancer. However, few studies have examined the relationship between OPN expression and gastric precancerous diseases, and the potential role of OPN in the formation and development of GC. We investigated the relationships between serum OPN levels and the risks of gastric cancer (GC) and its precancerous disease, to explore the diagnostic efficacy of serum OPN level for GC and atrophic gastritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…For the one-dimensional models, according to the results of our previous research, the cutoff values were set 7.0 for PGI/II 6 , 34.0 EIU for HpAb [positive, Biohit], and 2.6 ng/mL for OPN 16 , respectively. For the multi-dimensional models, the optimal cutoff points were calculated based on the highest specificity with sensitivity >0.7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the one-dimensional models, according to the results of our previous research, the cutoff values were set 7.0 for PGI/II 6 , 34.0 EIU for HpAb [positive, Biohit], and 2.6 ng/mL for OPN 16 , respectively. For the multi-dimensional models, the optimal cutoff points were calculated based on the highest specificity with sensitivity >0.7.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, compelling evidence from experimental and clinical studies suggested that OPN overexpression was associated with clinic-pathological features and prognosis of GC 29 31 . Our previous research, which focused on investigating the relationships between serum OPN levels and risks of GC together with its influencing factors, has found serum OPN expression was closely related to GC risks, suggested that it might be a useful marker for the discrimination of GC 16 . However, as OPN is widely expressed in a variety of tissues, including bone, cartilage, kidney, blood vessels, skin and other tissue 32 – 35 , it itself lacks organ specificity and can’t be positioned.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 There is no specific clinical manifestations among CAG patients; however, most patients have the clinical symptoms of pain, fullness, nausea, belching, constipation, and diarrhea in the epigastrium. 1 , 2 Recently, the incidence, prevalence, and mortality of CAG in China have been found to be growing because of the increasing infection rate of helicobacter pylori (Hp), aggravation of environmental pollution, and unhealthy lifestyles such as high-fat and high-salt diet, shortage of fruits, and vegetables intake. 3 Although the pathogenesis of CAG is still unclear, many research works have proved that long-term changes in gastric mucosa of CAG are one of the risk factors for gastric cancer (GC).…”
Section: Introductionmentioning
confidence: 99%